Elaboración de un curso virtual en moodle, como apoyo didáctico para el proceso de enseñanza aprendizaje del bloque la cultura, de la asignatura de Estudios Sociales, para los estudiantes de octavo año de educación general básica, de la unidad educativa San Francisco de Asís de la ciudad de Loja, periodo 2014-2015 - Sánchez Jaramillo, Ángel David (2016)
This thesis work was based on the needs and requirements at Unidad Educativa “San Francisco de Asís” because there isn`t enough knowledge on new technological support tools to improve the process of teaching/ learning in the subject of Social Studies. Facing this problem, the present research has as an objective to: Development an online course in Moodle, as a teaching support for the teaching-learning process of the Culture block, in the subject of social studies for students in eighth year of basic general education, the main purpose was to improve and enhance the teaching work and give a new and innovative learning resource to students, that allows them to improve their knowledge and achieving significant learning in each of them. For the development of the virtual course, I used the Dynamics methodology following phases about: Educational Design, Production, Realization, Implementation and Evaluation. In the first phase I used Technical survey in which took part 38 students and their teacher, this Technical survey let us identify weaknesses in learning about Culture block. Related this basis I drew up the virtual course in Moodle, which includes teaching resources such as: images, sounds, videos about content, learning and evaluation activities. The virtual course was socialized with the teacher and her students to demonstrate that all expected objectives are accomplished and train them to handle it correctly. The evaluation outcomes are positive, because the incorporation of the virtual course is considered necessary, as a teaching resource for Social Studies, for its good characteristics about motivation, interaction, visual quality and content structure. The virtual course is an interactive teaching resource that enables to accomplish with the objectives, content and curriculum skills of the subject. Educational authorities are encouraged to implement this resource to improve the process of teaching learning in the school